Degradation behaviors of cement-free corundum-spinel castables in Ruhrstahl Heraeus refining ladle: Role of infiltrated steel. Issue 22 (15th November 2021) - Cheng, Yaping; Zhang, Yu; Li, Yuanyuan; Chen, Junfeng; Xiao, Junli; Wei, Yaowu; Liu, Guangping; Li, Guangqiang; Zhang, Shaowei; Li, Nan
Abstract: Chemical attacks and structural spalling dominated the degradation process of the refractory lining in refining ladle. In the present work, we have fabricated a cement-free gel-bonded corundum-spinel castables and examined the degradation behavior in contact with the molten steel/slag. Further, the role of infiltrated steel/slag associated with cracks on the spalling behavior were elucidated. The stress cracks formed on the corroded interface, providing a permeation pathway for molten corrosive species and acting as a sub-surface for further corrosion. Infiltrated steel contributed to the formation of composite (Mg, Fe)Al2 O4 spinel and led to an additional corrosion and induced a large structural spalling. Besides, macro-scale structural spalling of the refractory lining and microscale spalling of aluminate aggregates were discussed in detail, respectively.